Quintic B-spline polynomial for Solving Bagely-Torvik Fractional Differential Problems - Hamasalh, Faraidun K.; Hamzah, Karzan Abdulrahman (Sulaimani Journal for Pure and Applied Sciences, 2020)
In this paper, we use Quintic B-spline function to drive some error analysis of fractional derivatives and finding numerical solution for certain type fractional differential equations. It is know that a class of control points related to the modulus of continuity can be found by matrices operations, and discuss the error estimations for numerical solutions finding by using quantic B-spline to be in good agreement with the exact solutions. Results are shown graphically and illustrated the method by several examples.
Keywords: Quintic B- spline; control points; Fractional derivative; Taylor series; Convergence analysis